Metode Cooperative Learning pada Proses Pembelajaran Paket A Kelas Komunitas di PKBM Homeschooling Pena Surabaya - Ummah, Alfi Mashlahatil; Susilo, Heryanto (J+PLUS UNESA, 2024)
The learning process will of course be very active and interactive if the learning method used is effective. The learning method that can be used is the cooperative learning method, this method will make the learning process more active. This method will unite students in one group with constant supervision and guidance from the tutor. This study used qualitative research methods. Data was collected using in-depth interview, observation and documentation data collection techniques. The data analysis techniques used are data reduction, data presentation and conclusions. Meanwhile, the criteria for data validity use a credibility test with triangulation of sources, techniques, time, as well as member checks, dependability tests, transferability tests, and confirmability tests. The results of this research explain the steps in implementing the cooperative method by tutors at the Homeschooling Pena community learning activity center, namely "designing lesson plans, making observation sheets, educators guiding and directing students in learning activities, educators giving students the opportunity to present the results of their work".